(untitled) (Revista Brasileira Multidisciplinar, 2009)
The goal of this investigation was to simulate the water quality of São Simão stream, in different sceneries, using the QUAL2K model to subsidize the technical-economical and environmental analysis of possible alternatives to wastewater treatment in the city. The alternatives were analyzed using an interactive matrix originally developed; it was constituted of evaluation criteria and their weights, essentially linked to the reality of the place. After the model was calibrated, simulations of different sceneries were carried out, showing the need of the implantation of alternatives that reach at least 75% of efficiency to attend the current legislation. Finally, the result shows that the UASB treatment system was the most applicable to the reality of the town.